Kultura zaufania w organizacji. Istota – potrzeba – kształtowanie - Czajkowska, Maria (Annales. Etyka w Życiu Gospodarczym, 2008)
The article brings up the problem of making use of trust in organization management. Modernorganizations and the conditions of their functioning enforce some inevitable changes in different areasof their activity. An attempt at adapting to these changes may be shaping trust cultureand an opportunity to use this tool in organization management. The article contains elements of trusttheory as well as organizational culture theory. It also presents an effort put into defining the guidelinesfor organization management concerning the trust culture shaping (on the basis of a theoretical model)and positive aspects of trust existing in an organization as well as a possibility of using itin management science as an effective tool.